Design hydrology and sedimentology for small catchments - Haan, C. T. 1941- (Academic Press, 1994)
The Clean Water Act, with its emphasis on storm water and sediment control in urban areas, has created a compelling need for information in small-catchment hydrology. Design Hydrology and Sedimentology for Small Catchments provides the basic information and techniques required for understanding and implementing design systems to control runoff, erosion, and sedimentation. It will be especially useful to those involved in urban and industrial planning anddevelopment, surface mining activities, storm water management, sediment control, and environmental management. This class-tested text, which presents many solved problems throughout as well as solutions at the end of each chapter, is suitable for undergraduate, graduate, and continuing education courses. In addition, practicing professionals will find it a valuable reference. Anderson/Woessner: APPLIED GROUNDWATER MODELING (1992) Shuirman/Slosson: FORENSIC ENGINEERING (1992) de Marsily: QUANTITATIVE HYDROGEOLOGY (1986) Selley: APPLIED SEDIMENTOLOGY, THIRD EDITION (1988) Huyakorn: COMPUTATIONAL METHODS IN SUBSURFACE FLOW (1986) Pinder: FINITE ELEMENT MODELING IN SURFACE AND SUBSURFACE HYDROLOGY (1977) Key Features * Covers major new improvements and state-of-the-art technologies in sediment control technology * Provides in-depth information on estimating the impact of land-use changes on runoff and flood flows, as well as on estimating erosion and sediment yield from small catchments * Presents superior coverage on design of flood and sediment detention ponds and design of runoff and sediment control measures.
Keywords: Watershed management.; Sediment control.; Runoff.; Hydrology.; elektronické knihy; electronic books